Investigation of coronary arteries in the porcupine (Hystrix cristata) by latex injection and angiography - Atalar, Ö; Yilmaz, S; Ilkay, E; Burma, O (Urban & Fischer Verlag, 2003)
Coronary arteries were investigated in the porcupine by means of angiography performed on each of 5 adult porcupines (3 male, 2 female) which was followed by injection of a colored latex mixture from the aortic arch for the demonstration of these arteries. The results showed that the aorta branched out at the level of the cardiac outlet to form the left and right coronary arteries and right ramus coni arteriosi. Coronary arteries coursed and ramified in the myocardium. The left coronary artery divided to form the paraconal interventricular artery and left circumflex artery when it reached the coronary sulcus. The interventricular septum was vascularized by the septal branch of the paraconal interventricular artery and by the small septal branches. The left and right coronary arteries gave off all the branches reported in the literature for other species. When the ramus coni arteriosi originates from the right coronary artery, it is designated a third coronary artery. In conclusion, it was found that the coronary arteries of the porcupine had an intramyocardial course as in other rodents. Pie coronary supply of the heart represented a left coronary type which was similar to those of carnivores and ruminants. The results of this study may contribute to the data in this area of science.
Keywords: arterial supply; heart; coronary artery; porcupine